The Bawean communities of Gombak: a historical analysis of migration, social integration and economic contributions - Mohd, Siti Hadija; Mansor Majdin, Mohamad Firdaus; Sulkafle, Mohamad Hazizie (Asian Scholars Network (ASNet), 2025)
This study investigates the historical trajectory of Bawean communities in Kampung Simpang Tiga and Kampung Sungai Chinchin, located in the Gombak district of Selangor, Malaysia. Drawing on interviews from existing documentaries as well as published materials, it reconstructs the migration of the Bawean people from Bawean Island, Indonesia, to Gombak. The paper examines their settlement process, adaptation to local life, and occupational patterns during the 20th century. Although Bawean communities have lived in Malaysia for more than a century, their presence remains insufficiently represented in Malaysian historiography. Through selected interviews and academic works, this research traces how Bawean settlers navigated issues of land, livelihood, and identity within Malaysia’s shifting socio-political setting. Primary data collected throughout 2024 to 2025, which includes personal communications and interviews with residents of Kampung Sungai Chinchin, are combined with video documentaries and secondary writings. On top of that, the analysis highlights the ways Bawean identity has been maintained in certain aspects and reshaped in others, situating these experiences within broader migration patterns in Southeast Asia.